Pijat Bayi Cara India dan Johnson Meningkatkan Berat Badan Bayi Lahir Rendah - Asmawati Gasma; Indriani Amin; Ros Rahmawati (Jurnal Kesehatan Manarang, 2021)
Low birth weight infant mortality is one of the causes of high infant mortality (AKB) in Indonesia. Infant mortality can be prevented by improving the quality of the baby's health through growth and development. One of the efforts to improve the quality of baby health. The study aims to prove the difference in BBLR BB increase through Indian and Johnson way baby massage. The method used is Quasy Experimen with pretest-posttes design. The population is a low birth weight baby born in RSIA Pertiwi Makassar period July – September 2018. The study sample numbered fourteen that met the criteria. Seven babies were massaged the Indian way and seven babies were massaged johnson's way. Massage is done twelve times at intervals three times a week. Fifteen minutes at a time. The instruments used are baby scales and observation sheets. Univariate data analysis showed the average increase in BB for Indian way baby massage was fifty-one percent,while theaverage weight gain for Johnson's way of baby massage was fifty-three percent. Statistical tests with mann-Whitney U, showed that there was no significant difference in BBLR BB increases between indian and johnson massage. The conclusion of this study is the indian and Johnson way baby massage can both increase BB BBLR.